Expression of complement C5a receptor and the viability of 4T1 tumor cells following agonist–antagonist treatment - Kosni, Nurneqman Nashreq; Ganti, Norhaifa; Mohd Noor, Mohd Hezmee; Abdul Razak, Intan Shameha; Md Ajat, Mohd Mokrish; Omar, Abdul Rahman (Medknow Publications, 2016)
Background: Complement system is theoretically believed to halt the progression of tumor by the activity of C5a/CD88. Protein C5a is a potent pro.inflammatory mediator that activates the complement system by binding to its receptor. Objectives: The purpose of this study is to determine the expression of the anaphylatoxin C5a receptor on 4T1 cell line and to study the viability of the cells after being treated with the C5a peptides. Materials and Methods: The cells 4T1 had undergone immunofluorescence staining, conventional polymerase chain reaction (PCR) and real-time PCR for the expression of determination part. Whereas Alamar Blue and MTT assays were conducted for the viability study of the cells. Results: The cells showed positive result in expressing the receptor of the C5a through immunostaining and PCR. The CT value recorded at initial dilution was 22.24. In cell viability assay, the cell was treated with C5a peptides, PMX205 and EP54. The purpose of this treatment was to see whether C5a had a direct effect on the cell itself using both assays. The result showed that PMX205, which is an antagonist, gave more effects towards the cell as compared with the treatment of EP54. Conclusion: This experiment shows the presence of C5a receptor on 4T1 cell line. We believe that the antagonist peptide is eligible to be used widely in cancer immunotherapy field; but in vivo studies need to be carried out first in the future, as it will determine how these drugs affect the tumor cell growth.